Effect of ion temperature on ion-acoustic solitary waves in a magnetized plasma in presence of superthermal electrons - Singh, S.V.; Devanandhan, S.; Lakhina, G.S.; Bharuthram, R. (My University, 2013)
Obliquely propagating ion-acoustic soliatry waves are examined in a magnetized plasma composed of kappa distributed electrons and fluid ions with finite temperature. The Sagdeev potential approach is used to study the properties of finite amplitude solitary waves. Using a quasi-neutrality condition, it is possible to reduce the set of equations to a single equation (energy integral equation), which describes the evolution of ion-acoustic solitary waves in magnetized plasmas. The temperature of warm ions affects the speed, amplitude, width, and pulse duration of solitons. Both the critical and the upper Mach numbers are increased by an increase in the ion temperature. The ion-acoustic soliton amplitude increases with the increase in superthermality of electrons. For auroral plasma parameters, the model predicts the soliton speed, amplitude, width, and pulse duration, respectively, to be in the range of (28.7–31.8) km/s, (0.18–20.1) mV/m; (590–167) m, and (20.5–5.25) ms, which are in good agreement with Viking observations.
Keywords: Ion temperature; Solitary waves; Superthermal electrons; Plasma waves; Ion-acoustic soliatry waves